PENGARUH SUPERVISI KEPALA SEKOLAH DAN PENGETAHUAN PEDAGOGIK TERHADAP KOMITMEN PROFESI GURU - Myta Widyastuti (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2016)
Abstract: The study reported here aimed to examine how the headmasters’ supervision and pedagogical knowledge actually affected professional commitment. It was a quantitative research with a causal study conducted on public junior high school teachers in 2013. The research were collected through means of survey in East Jakarta, involving 179 teachers as respondents that were selected through proportionate random sampling. The data for headmasters’ supervision and professional commitment variable were collected through questionnaire alongside written test for pedagogical knowledge variable. A path analysis was employed to analyze the data.The data analysis and interpretation indicates that (1) headmasters supervision had a positive direct effect to teachers professional commitment (2) pedagogical knowledge had a positive direct effect to teachers’ professional commitment, (3)and also headmasters supervision had a positive direct effect on the pedagogical knowledge of the teachers. Keywords: supervision, pedagogical knowledge, and professional commitment.